The Law Enforcement Reform Based on Pancasila Values: A Critical Review - Mambaya, Marthinus (Papua Law Journal, 2016)
The influence of colonial law is individual-liberal tempered as well as the globalization is capitalist-liberal tempered became a serious threat to the development of Indonesian law, because it raises the alienation syndrome of State laws from the values of life and upheld in a society that is Pancasila values, therefore the law reform of Indonesia became a necessity to do. This paper focuses on the reform in the field of typical law enforcement in Indonesia, where Pancasila as the ideological basis, in the logic of Stufenbau be the main touchstone which provides ontological, normative and operational frameworks for structuring better law enforcement and typical Indonesian. The principle of Almighty God becomes ontological framework for Indonesian people. Therefore, its existence is inter-related to the Almighty God as the source of value, truth and meaning. Just and civilized humanity is recognized as a ontological base and became the normative framework in order to enforce the law in a fair, civilized and humane, not oppressive character. It is operationalized within the framework of unity, not cause divisions, because all equal in the law as realized by acting wisdom and culminating in social justice for all citizens, social justice in favor of the weak.